Międzynarodowa polityka turystyczna - utopia, alternatywa czy konieczność? - Alejziak, Wiesław (Inernational Tourism Policy - Utopia, Alternative or Necessity?, 2005)
The article presents the concept and scope of contemporary tourism policy and initiates the discussion regarding the problem of, whether and to what extend, the so called megatrends in the development of civilization, which result in changing the modern world, influence tourism policy of countries. Basic concepts have been characterized, which point to the process of creating an international (global?) tourism policy. It has been underlined that its scope, forms of conducting it and the available instruments of its realization are not yet sufficiently developed, however, some global concerns resulting from the development of tourism (eg. the ongoing degradation of environment) emphasize international cooperation, as an important instrument in this area.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 11-39